2015
DOI: 10.1007/s11425-015-5084-3
|View full text |Cite
|
Sign up to set email alerts
|

Derivative formulas and Poincaré inequality for Kohn-Laplacian type semigroups

Abstract: As a generalization to the heat semigroup on the Heisenberg group, the diffusion semigroup generated by the subelliptic operator L :for σ an invertible m × m-matrix and {A l } 1≤l≤d some m × m-matrices such that the Hörmander condition holds. We first establish Bismut-type and Driver-type derivative formulae with applications on gradient estimates and the coupling/Liouville properties, which are new even for the heat semigroup on the Heisenberg group; then extend some recent results derived for the heat semigr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…) has been well studied in the literature, where M x T is an integrable random variable on R d , which is measurable in x ∈ R d when it varies, see for instance [1,15,25,26,28] and references within. Since the coefficients are distribution independent, we have (1.12)…”
Section: Introductionmentioning
confidence: 99%
“…) has been well studied in the literature, where M x T is an integrable random variable on R d , which is measurable in x ∈ R d when it varies, see for instance [1,15,25,26,28] and references within. Since the coefficients are distribution independent, we have (1.12)…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, 1 ∈ H 1,2 σ (µ 0 ) with E 0 (1, 1) = 0. Moreover, according to [14,Corollary 1.2], there exists a universal constant c > 0 such that the log-Sobolev inequality (1.3) holds for κ = t 0 c and β = 0 (see [31] for more results on functional inequalities). So, assumption (H) holds.…”
Section: Main Results and Examplesmentioning
confidence: 99%
“…In [52][53][54] it has been shown that if we assume Ric (M ) K for some K ∈ R, then there exists a Markovian coupling of Brownian motions (B t ) t 0 and B t t 0 on M starting at p and p such that…”
Section: 2mentioning
confidence: 99%
“…This construction is known as a coupling by parallel transport. This coupling can be constructed using stochastic differential equations as in [24,54], or by a central limit theorem argument for the geodesic random walks as in [52]. It turns out that the existence of the coupling satisfying (4.14) is equivalent to…”
Section: 2mentioning
confidence: 99%